Non-destructive allometric models for leaf area prediction of Jatropha curcas L. - Krishan Kumar Verma; Chhedi Lal Verma; Munna Singh (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Jatropha curcas received a lot of attention as a biodiesel feedstock in several countries around the world. The leaf area (LA) estimation is important for biological research due to its close relationship to soil fertility, plant physiological parameters, and photosynthetic efficiency. Allometric models for reliable and accurate models for estimating the leaf area of Jatropha curcas plants based on non-destructive measurements of leaf length (L), width (W), and/ or leaf margins length (P) were developed. Jatropha plant leaves were randomly selected for model construction to estimate the leaf area using L, W, and P leaf values. Simple and accurate equations were obtained, based on leaf width (AL = W1.795), R2 = 0.987, rib length (AL = L32.081), R2 = 0.989, width and rib length (AL = LW0.320), R2 = 0.997, rib length and leaf periphery segment (AL = LP1P120.274), R2 = 0.995, and half rib and width length (AL = LW/0.50.467), R2 = 0.994. The equations were accurate for estimating leaf area of small, medium, and large size of Jatropha leaves.